Estudo geológico e geotécnico de depósito antropogênico de resíduos na cidade de São Carlos - Oliveira, Vinicius Gustavo de (Universidade Federal de São Carlos, 2019)
Since ancient times, mankind to develop, has explored the physical environment, causing various changes in the planet, changing sedimentation rates, creating artificial grounds, or even generating voids in excavated areas, called deposits and manmade grounds. Among these deposits are the urban soils, formed in urbanized areas and that have their origin linked to the anthropic action. Although these deposits have become increasingly numerous, their geotechnical and geological properties are still unknown. The objective of this work is to survey the geological and geotechnical characteristics of an anthropogenic area, which consists of an area that was landed with constructional waste, as well other types of waste. As methodological, a bibliometric analysis was first carried out, to understand the evolution of the anthropogenic deposit approaches; bibliographic survey; digital image analysis; mapping of the manmade grounds that occur in the study area; geotechnical field tests in the areas of natural soil, surface residues and landfills of construction waste, with dynamic penetrometer, infiltration tests, electrical resistivity (geophysics), characterization of wastes. It was possible to delimit the area of occurrence of construction and demolition waste landfill, determine its depth, contextualize the evolution, and to determine the characteristics of this surface area. The waste in the landfill area has been contributing to the formation of contaminant plumes. Also, the discharge of sewage into the Água Quente stream has generated a deep plume of contaminants, capable of reaching the deep wells of groundwater captation. As the natural soils, and the materials of the landfill area have draining characteristics, it is concluded that the site is not ideal place to a construction waste landfill.
Geological and Geotechnical study of a anthropogenic waste deposit in the city of São Carlos
Keywords: Depósitos antropogênicos; Depósitos tecnogênicos; Eletrorresistividade; Resíduos de construção civil; Ensaios geotécnicos; Anthropogenic deposits; Technogenic deposits; Anthropocene; Construction waste; Geotechnical tests; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA